Institutional Factors and Academic Staff Job Performance in Public Universities in Southwest, Nigeria - ADESOLA, Michael Babatunde; EKUNDAYO, Haastrup Timilehin (Journal of Education and Practice, 2022)
Purpose: This study investigated the relationship between institutional factors and academic staff job performance in Southwest, Nigeria. The study examined the level of academic staff job performance in public universities. The study also examined the extent to which the institutional factors are favourable in the Universities. The study specifically examined relationship between institutional factors such as physical facilities and staff workload. Methodology: The study adopted descriptive research design of the survey type. The population of this study consisted of 12,844 Academic Staff of public universities in Southwest, Nigeria. The sample of this study consisted of 90 Heads of Departments and 900 academic staff of public universities. Multi-stage sampling procedure involving simple random sampling technique, stratified random sampling technique and proportionate random sampling technique were used in the selection of the sample for the study. Two instruments tagged "˜Institutional Factor Questionnaire (IFQ) and the Academic Staff Job Performance Questionnaire (ASJPQ)' were used to collect data from the respondents. Findings: A reliability coefficient of 0.78 was obtained for the Institutional Factor Questionnaire and 0.76 was obtained for the Academic Staff Job Performance Questionnaire. The data collected were analysed using percentages, frequency count, Mean, Standard Deviation and Pearson Product Moment Correlation. All hypotheses formulated were tested at 0.05 level of significance. The study revealed that level of academic staff job performance was high in public universities in Southwest, Nigeria. It also revealed that status of institutional factors was favourable. Institutional factors variables such as physical facilities and staff workload largely determined academic staff job performance in public Universities in southwest, Nigeria. Unique Contribution to Theory, Policy and Practice: In view of the fact that the status of institutional factors was favourable in public universities in southwest, Nigeria, owners of public institutions in Southwest Nigeria should prioritize adequate physical infrastructure to improve the quality of teaching and research. Also, academic personnel should be assigned assignments based on competency and not overworked.